Amish Homestead : A Seat by the Hearth - Book 3 - Clipston, Amy (Grand Rapids, Michigan : Zondervan, 2018)
"In the third installment of Amy Clipston's Amish Heirloom series, Priscilla Allgyer returns to the Amish community she'd dreamt of escaping and learns the hard lessons of love and forgiveness from a surprising source"--
Keywords: Amish -- Fiction; Man-woman relationships -- Fiction; Forgiveness -- Fiction; Lancaster County (Pa.) -- Fiction; Religious fiction; Romance fiction